Implementation of Classroom Audio System to Increase Learning Effectiveness at Khazanah Kebajikan Vocational School : Implementasi Sistem Audio Ruang Kelas untuk Meningkatkan Efektivitas Pembelajaran di SMK Khazanah Kebajikan - Muhammad Wahyu Taqwana; Ryan Aryadi; Oki Supriyadi; Ojak Abdul Rozak (Institut Riset dan Publikasi Indonesia, 2025)
The availability of an adequate audio system is an important component in supporting the effectiveness of communication and learning in schools. SMK Khazanah Kebajikan is still facing limited audio facilities so that the sound of announcements and material delivery is not heard evenly in the classroom. This Community Service activity aims to improve the quality of communication and the teaching-learning process through the installation of a standardized classroom audio system. The stages of the activity include needs and permitting surveys, site reviews, preparation of tools and materials, participant training, device installation, sound quality testing, and overall evaluation. The installation was carried out by Electrical Engineering students of Pamulang University as a form of application of knowledge and collaboration with the school. The test results showed a significant improvement in sound quality, characterized by more even audio distribution, clearer voice, and improved communication comfort in learning activities. The evaluation of the activity also showed an increase in participants' understanding from 40% to 80% after participating in the installation training. This program has a direct impact in the form of increasing the efficiency of school communication while increasing student competence in the practice of audio system installation. This activity is expected to be sustainable and can be replicated in other schools to support the improvement of the quality of educational facilities.